2021
DOI: 10.1126/science.abj1028
|View full text |Cite
|
Sign up to set email alerts
|

Coherent perfect absorption at an exceptional point

Abstract: Absorbingly exceptional Most oscillating systems have a resonance or multiple resonances at which they ring out and are most sensitive to excitation. In non-Hermitian systems, open systems with gain and loss, the resonances have been found to coalesce into an exceptional point when the gain and loss can be engineered. Complementing these resonant exceptional points, Wang et al . show that controlling the absorption of a coupled microresonator system can produce a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(106 citation statements)
references
References 70 publications
(39 reference statements)
0
94
0
Order By: Relevance
“…Even, programmable photonic circuits that can be reconfigured using a software have been demonstrated [253], which moves photonics along the similar path from ASIC (application-specific integrated circuits) to FPGA of electronics. From a basic science perspective, research on topological systems (see Chapter 8 in [9]), non-hermitian systems (see Chapter 7 in [9]), and devices based on exceptional point physics [146] provides many new phenomena and device concepts [254]. Thus, at the end of this 30-year-long journey, I belive that photonics made with complex silicon circuitry has yet to unveil new physics from which new understanding and new applications can emerge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even, programmable photonic circuits that can be reconfigured using a software have been demonstrated [253], which moves photonics along the similar path from ASIC (application-specific integrated circuits) to FPGA of electronics. From a basic science perspective, research on topological systems (see Chapter 8 in [9]), non-hermitian systems (see Chapter 7 in [9]), and devices based on exceptional point physics [146] provides many new phenomena and device concepts [254]. Thus, at the end of this 30-year-long journey, I belive that photonics made with complex silicon circuitry has yet to unveil new physics from which new understanding and new applications can emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Tuning of the coupling and of the Fano lineshape asymmetry is possible by using nonlinear effects [142]. Clearly, these are only few observations of the phenomena associated to non-Hermitian photonic systems, more studies have been reported in the literature, see e.g., [143][144][145][146].…”
Section: Hermitian and Non-hermitian Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such open or non-Hermitian systems generally have complex eigenvalues and may exhibit exceptional points [ 235 , 236 , 237 ]. Systems tuned to an exceptional point are extremely sensitive to perturbations [ 238 , 239 ]. In recent years, there has been tremendous progress in the theory and experimental implementations of non-Hermitian photonics, including all-lossy optical systems as well as parity-time symmetric systems [ 236 , 240 ].…”
Section: Metamaterials and Metasurfaces: Glimpses Of New Trendsmentioning
confidence: 99%
“…However, a system with PT symmetry possesses purely real eigenspectra in certain regimes, whereas the eigenstates are non-orthogonal to each other. Over the past few years, PT-symmetric systems featuring balanced gain and loss profiles have been studied in optics 1 15 , optomechanics 16 , 17 , optoelectronics 18 and acoustics 19 21 and have initiated a number of exotic effects and applications including electromagnetically induced transparency 1 , 2 , coherent perfect absorption-lasing 3 6 , topological light steering 7 , single-mode lasing 8 10 , ultrasensitive sensors 11 13 , opto-electronic microwave generation 18 and non-reciprocal photon 14 , 15 and phonon 21 transmission.…”
Section: Mainmentioning
confidence: 99%